Addressing Corruption and Government Challenges: The Case of Uganda’s Strategic Developments Policies - Nambassa, Gloria; Qodir, Zuly (Department of International Relations, Brawijaya University, 2024)
A country’s development is fundamentally influenced by how strategic its policies are in addressing citizens' pressing needs. These policies reflect the actions, or inactions, of governments. National Development Policies focus on crucial socio-economic sectors to bring significant changes. This paper examines Uganda’s National Agriculture Policy of 2013 and Renewable Energy Policy of 2007. We analyze how Uganda’s strategic policy implementation combats corruption and addresses developmental shortcomings. The National Agriculture Policy aims to enhance agricultural productivity and ensure food security, while the Renewable Energy Policy promotes sustainable energy solutions and reduces dependency on non-renewable sources. By prioritizing these sectors, Uganda seeks to foster socio-economic development, mitigate corruption, and improve overall governance. This study highlights the successes and challenges in implementing these policies, providing insights into the role of strategic policy-making in addressing corruption and development issues in Uganda, ultimately contributing to the country's socio-economic advancement.